1978
DOI: 10.1136/jnnp.41.12.1135
|View full text |Cite
|
Sign up to set email alerts
|

Neurological asymmetries immediately after unilateral ECT.

Abstract: Diseases, Queen Square, London S U M M A R Y Twenty-nine right handed patients were examined neurologically before and immediately after each of 62 unilateral ECTs to the dominant and non-dominant hemispheres. Most convulsions were followed by signs of transitory neurological dysfunction referable to the treated hemisphere. These signs included deep tendon reflex asymmetry, hemiparesis, tactile and visual inattention, and homonymous hemianopia. After treatment to the right hemisphere some patients had left vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…3 Proposed mechanisms for neuronal dysfunction underlying such deficits include transient hyperpolarization of cells, cellular toxicity mediated by N-methyl-D-aspartate receptors, and localized changes in cerebral blood flow and metabolism. 2 Transient hemiparesis and other focal neurologic dysfunction immediately after ECT have been previously documented as both single case reports and as a case series. 4 Presumably, the mechanism of postictal focal dysfunction after ECT is similar to that of postictal focal dysfunction after spontaneous seizure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Proposed mechanisms for neuronal dysfunction underlying such deficits include transient hyperpolarization of cells, cellular toxicity mediated by N-methyl-D-aspartate receptors, and localized changes in cerebral blood flow and metabolism. 2 Transient hemiparesis and other focal neurologic dysfunction immediately after ECT have been previously documented as both single case reports and as a case series. 4 Presumably, the mechanism of postictal focal dysfunction after ECT is similar to that of postictal focal dysfunction after spontaneous seizure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism remains unclear. 2,5,6 However, in the former, cerebrovascular ischemia was the identified mechanism; whereas in the latter, cerebral imaging was not obtained. Of note, the duration of our patient's appreciable deficit was shorter relative to that usually seen in epileptics after spontaneous focal seizures; a finding reported previously in a larger case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kriss et al (1978) examined a variety of neurological effects after RUL and LUL ECT in 29 right‐handed patients. They found that patients tended to have transient muscle weakness, reduced reflexes, and visual attention deficits contralateral to the treated side.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is less well known that ECT may also induce transient neurological adverse effects; these may be lateralizing, such as when unilateral ECT is administered. 1 Transient blindness after ECT, albeit rare, is one such neurological adverse effect. To the best of our knowledge, there have been only 2 cases of ECT-induced blindness reported in literature.…”
mentioning
confidence: 99%